Pembinaan Prestasi Atlet Pencak Silat Se-Kabupaten Rembang (Universitas Negeri Semarang, 2022)
In general, the development of achievement has not been in accordance with the results obtained, which are not as expected. The problem in this research is that the achievements of the pencak silat athletes in Rembang Regency have not been as expected because the training has not been clearly programmed and structured. The purpose of this study was to determine the achievement development of pencak silat athletes in Rembang Regency. This research method uses descriptive qualitative with methods of observation, interviews and documentation. The research sources consist of 1 chairman of the National Association, 1 chairman of IPSI, 3 college coaches and 15 athletes from 3 different colleges. This research was conducted in Rembang Regency, the data analysis technique used was data triangulation, data analysis, data reduction, data presentation and conclusions drawn. The results showed that (1) the stages of coaching: massing was carried out if the admission of new students to school was through the mass media, the nursery was carried out with a match test as a benchmark for the recruitment of athletes, the achievement strategy was implemented with special training, (2) there was a training program but it was not written down. , (3) the condition of the athletes is not appropriate, (4) the existing facilities still need updating and additions, (5) the research has not been running as it should, (6) the competition conducts try outs and try ins (7) the organization is managed by members of each college the chosen ones, (8) the existing funds at IPSI are obtained from sponsored KONI and college fees under the auspices of Ipsi, for colleges it comes from membership fees and schools that have pencak silat colleges under the auspices of IPSI. The conclusion of this research is that the development of pencak silat achievement in Rembang Regency does not work as expected or the system implemented has not given the desired results. Suggestions that can be given (1) for fighters in Rembang Regency to pay more attention to the pattern of coaching that has been running so that the objectives of the coaching are obtained maximally, (2) the pencak silat coach to always learn new things in order to add knowledge so that it can be applied to his athletes, (3) the Pencak silat college of Rembang Regency to add more existing facilities to facilitate the athlete coaching process.